Sosialisasi Pengaruh Asupan Gizi untuk Mencegah Stunting Pada Masyarakat Desa Timbang Lawan - A.Irma Putri Meilina; Siti Salamah Br Ginting; Miftah Kurnia Arfah Pulungan; Saputri Saputri; Fadhil Abdullah (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Stunting is a chronic nutritional problem that has a serious impact on child development. This study aims to gain a deep understanding of the perceptions, knowledge, and practices of the community in Timbang Lawan Village regarding nutritional intake and stunting prevention. Through a qualitative approach using participatory observation and in-depth interviews, this study reveals the factors influencing feeding practices for toddlers, the challenges faced, and effective strategies to improve nutritional intake. The results show that low knowledge about nutrition, limited access to nutritious food, and socio-cultural factors are the main challenges in stunting prevention efforts.